Fighting Cancer with Knowledge and Hope : A Guide for Patients, Families, and Health Care Providers - RICHARD C. FRANK (Yale University Press, 2013)
Being mortal can be a blessing if we believe an old Greek myth. In that story, a man who did not want to die begged the gods to grant him immortality and eternal youth. Tired of his pestering, they gave him his request. He grew old, watched his family die, and saw his friends pass away. The people he loved were gone, leaving him lonely and in despair. He again begged the gods, this time to allow him to die. They agreed, and he died the happiest man on earth.